ANALISIS SIFAT FISIS AGREGAT HALUS PASIR DAN LIMBAH PLASTIK - Muhtarom Riyadi; Tri Wulan Sari (Politeknik Negeri Jakarta, 2021)
Based on SNI 03-2847-2002, concrete can be defined as a mixture of cement, fine aggregate, coarse aggregate, water, and with or without other additives. The purpose of this study was to analyze the physical properties of fine aggregate sand and plastic waste such as SSD specific gravity, SSD specific gravity, bulk density, sieve analysis, moisture content, and sludge content. According to the Indonesian National Standard (SNI), the method used is the observation method by conducting direct testing in the laboratory. The results obtained indicate that the study of fine aggregate sand by testing SSD bulk specific gravity, bulk density, sieve analysis, moisture content, and silt content meet the standard specifications for making concrete. At the same time, the research conducted on the fine aggregate of plastic waste did not meet the specifications. Keywords: Aggregate, Physical Properties, Sand, Plastic Waste.